Analisis Pengakuan Pendapatan Jasa Outsourcing PT. Sukses Sejahtera Bersama Indonesia Berdasarkan PSAK No. 115 - Fiya Wardhatul Islamyi; Siti Sundari (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
PSAK No. 115 regulates revenue recognition from contracts, which are legally enforceable agreements between the two parties. PT SSBI earns revenue from work contracts and management fees. The revenue earned must be recognized in accordance with the applicable and latest accounting standards, namely PSAK No.115 concerning Revenue from Contracts with Customers. This study aims to determine whether revenue recognition at PT SSBI is in accordance with PSAK No.115. This research uses descriptive and comparative qualitative methods, and data collection techniques in the form of interviews and documentation. The company records revenue when the obligation has been fulfilled. This is in accordance with PSAK, where revenue can only be recognized after the obligation has been settled. After comparison, the stages of revenue recognition at PT SSBI are in accordance with the stages of revenue recognition according to PSAK No. 115, and in the contract several provisions have been included and revenue recognition is in accordance with PSAK No. 115.